Evidentiality in early modern English medical treatises (1500-1700) - Whitt, Richard J. (de Gruyter, 2016)
This study investigates diachronic trends in the use of evidential markers in Early Modern English medical treatises (1500-1700), with data drawn from the Corpus of Early Modern English Medical Texts. The state of medical thought and practice in Early Modern England is discussed, with particular focus on the changing role that Scholasticism played during this period. The nature of evidentiality and types of scholastic vs. non-scholastic evidence are given attention, and quantitative results are outlined. The results are then discussed in light of discursive and typological considerations.